Association between disability, social support and depressive symptoms in Chinese older adults: A national study - Gang Tian; Rui Li; Yiran Cui; Tong Zhou; Yan Shi; Wenyan Yang; Yulan Ma; Jingliang Shuai; Yan Yan (Frontiers in Public Health, 2022)
ObjectiveDisability and social support can impact depressive symptoms of the elderly. Yet, studies infrequently discuss the moderating role of social support when evaluating the association between disability and depressive symptoms. The purpose of this study was to explore the association between disability, social support, and depressive symptoms among the Chinese elderly, and further examine the moderating effect of social support.Materials and methodsUsing the 2018 Chinese Longitudinal Healthy Longevity Survey (CLHLS) data set, we finally selected 9,231 Chinese elderly after screening. The Center for Epidemiologic Studies Depression Scale (CESD-10) was used to evaluate depressive symptoms in the elderly. Disability was measured by basic activities of daily living (B-ADL) and instrumental activities of daily living (I-ADL). Social support included contact with family and friends, sick care, and money received, measured by five self-reported questions. We used multiple linear regression and moderating model to explore the association between disability, social support, and depressive symptoms.ResultsA total of 9,231 patients were included in this study, and approximately 26.75% of the elderly had depressive symptoms. Study found that depressive symptoms were associated with social support (βB−ADL = −0.108, 95% CI: −0.168– −0.047; βI−ADL = −0.098, 95% CI: −0.156– −0.039), βB−ADL (β = 0.296, 95% CI: 0.248−0.343) and I-ADL (β = 0.174, 95% CI: 0.152–0.195). Moreover, the result also showed that social support moderated the effects of B-ADL (βB-ADL*socialsupport = 0.034, 95% CI: 0.014–0.053, F = 11.57, p = 0.001) and I-ADL (βI-ADL*socialsupport = 0.025, 95% CI: 0.017–0.033) on depressive symptoms.ConclusionsThe study suggests that disability and social support can affect depressive symptoms, and social support moderates the effect of disability on depressive symptoms. Therefore, taking effective measures to reduce the elderly disability rate of disability and increase their social support are necessary condition for realizing mental health.